2020
DOI: 10.1021/acsami.0c13691
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Flexible Surface-Enhanced Raman Scattering (SERS) Sensors with High Stability and Signal Homogeneity

Abstract: Flexible surface-enhanced Raman scattering (SERS) sensors have attracted great attention as a portable and low-cost device for chemical and bio-detection. However, flexible SERS sensors tend to suffer low signal spatial homogeneity due to the uneven distribution of active plasmonic nanostructures (hot spots) and quick degradation of their sensitivity due to low adhesion of hot spots and flexible substrates during fast sampling. Herein, a large-area (20 × 20 cm 2 ) polyimide (PI)-based SERS sensor is exploited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(38 citation statements)
references
References 51 publications
(71 reference statements)
0
38
0
Order By: Relevance
“…This method typically involves in-situ chemical reduction of noble metal precursors physically dispersed in a flexible and adsorptive matrix, such as paper or textile. [109][110][111][112] For example, Ge, et al reported a large-scale synthesis of flexible cotton SERS wipes for trace analysis of surface residues. 113 The cotton SERS wipes were produced by dipping cotton sheets in AgNO 3 solution and then in a solution of ascorbic acid reducing agent, which led to the formation of Ag nanoparticles on the surface of the cotton fibers.…”
Section: In-situ Formation Of Plasmonic Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…This method typically involves in-situ chemical reduction of noble metal precursors physically dispersed in a flexible and adsorptive matrix, such as paper or textile. [109][110][111][112] For example, Ge, et al reported a large-scale synthesis of flexible cotton SERS wipes for trace analysis of surface residues. 113 The cotton SERS wipes were produced by dipping cotton sheets in AgNO 3 solution and then in a solution of ascorbic acid reducing agent, which led to the formation of Ag nanoparticles on the surface of the cotton fibers.…”
Section: In-situ Formation Of Plasmonic Nanoparticlesmentioning
confidence: 99%
“…swab dry sample for ex-situ analysis 0.13 ng (ClO4 -), 0.13 ng (ClO3 -) and 0.11 ng (NO3 -) on aluminum foil Ag@Au NPs polyimide film [110] in-situ growth 8.7% (30 points on one substrate)…”
Section: One-pot Formation Of Flexible and Plasmonically Filmsmentioning
confidence: 99%
“…SERS measurements typically utilize the induced surface plasmons on a metal surface to chemically or physically enhance the intensity of Raman scattering [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. SERS is an ultrasensitive vibrational spectroscopic technique used to detect molecules near the surface of plasmonic nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Using SERS of individual Ag colloidal NPs can achieve optical detection and spectroscopy of single molecules and NPs at room temperature [ 2 ]. Flexible SERS sensors were achieved through the fabrication of Ag–Au core-shell NPs based on chemical reduction and Galvanic replacement processes on a polyimide (PI) substrate [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation